السرطان في المخيال الاجتماعي الجزائري - بن عامر, وسيلة; حلاسة, فايزة (Changement Social; No 4 (2018): revue change social, 2018)
أن لكل مجتمع من المجتمعات نمط خاص بهم نالثقافة،لذانجد أن تعريف المرضيختلفمنمجتمعلآخرحسبنمطهالثقافي،وأيتطوراجتماعيفيهذاالمجتمعإنمايعنيفيالتصورالثقافيللمرض. ونحن في هذه الورقة البحثية سنسعى لإبراز الأهمية في التكامل بين علم الانثروبولوجية الطبية وعلم النفس في ميدان العلاج النفسي لمرض العصر "السرطان". لكونه مرضا عضويا بنيت حوله أساطير متعددة ومتفرقة بعدد شعوب العالم والتي تتحكم في القابلية للشفاء وتحدد مصير المريض. As for culture, it is ostensible every nation has its own particular interpretation to that issue. That is why when it comes to define a disease , the latter may vary from  one nation to another. Likewise, the understanding of any disease is relevant to the nation’s   development. Thus, in this research paper,  we have sought to outline the correlation between two disciplines Anthropology and Psychology for one of these diseases, cancer, from a psychological perspective. Such a perspective has been guided by the great stories and legends  of different peoples who have strived to provide many ways on how to cure this disease and give also a hope to the patients to recover.